Effect of stress gene-by-environment interactions on hippocampal volumes and cortisol secretion in adolescent girls. (April 2019) - Malhi, Gin S; Das, Pritha; Outhred, Tim; Dobson-Stone, Carol; Irwin, Lauren; Gessler, Danielle; Bryant, Richard; Mannie, Zola
Objective: Adolescence is a time of increased susceptibility to environmental stress and mood disorders, and girls are particularly at risk. Genes interacting with the environment (G × E) are implicated in hypothalamic-pituitary-adrenal axis dysregulation, hippocampal volume changes and risk or resilience to mood disorders. In this study, we assessed the effects of stress system G × E interactions on hippocampal volumes and cortisol secretion in adolescent girls. Methods: We recruited 229 girls aged 12–18 years, and scans were obtained from 202 girls. Of these, 76 had been exposed to higher emotional trauma (abuse or neglect). Hippocampal volumes were measured using Freesurfer and high-resolution structural magnetic resonance imaging scans. Saliva samples were collected for measurement of cortisol levels and genotyping of stress system genes: FKBP5, NR3C1 (both N = 194) and NR3C2 ( N = 193). Results: Among girls with the 'G' allelic variant of the NR3C1 gene, those who had been exposed to higher emotional trauma had significantly smaller left hippocampal volumes ( N = 44; mean = 4069.58 mm 3, standard deviation = 376.99) than girls who had been exposed to minimal emotional trauma with the same allelic variant ( N = 69; mean = 4222.34 mm 3, standard deviation = 366.74). Conclusion: In healthy adolescents, interactions between emotional trauma and the 'protective' NR3C1 'GG' variant seem to induce reductions in left hippocampal volumes. These G × E interactions suggest that vulnerability to mood disorders is perhaps driven by reduced 'protection' that may be specific to emotional trauma. This novel but preliminary evidence has implications for targeted prevention of mood disorders and prospective multimodal neuroimaging and longitudinal studies are now needed to investigate this possibility.